Eugenio d'Ors y Mircea Eliade - Díez de Velasco, Francisco (Archaeus, 2009)
Central and Eastern European Online Library - CEE journals, documents, articles, periodicals, books available online for download, Zeitschrfitendatenbank, Online Zeitschriften, Online Zeitschriftendatenbank